Penerapan Strategi Pembelajaran Berbasis Kepedulian Lingkungan untuk Meningkatkan Karakter Peduli Lingkungan Siswa Kelas III SD Negeri 133 Parmompang - Siti Marwiyah; Ali Yusron; Marwah Lubis (Universitas Muhammadiyah Mataram, 2026)
Abstract: This study aims to analyze the strategies of classroom teachers in fostering environmental awareness among third-grade students at SD Negeri 133 Parmompang and identify factors that support and hinder its implementation. The study used a qualitative descriptive approach with third-grade teachers, principals, and students as subjects. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that teachers implemented direct learning strategies, role models, habituation through routine